Analysis of Banking Sector of Kazakhstan in terms of profitability: Islamic versus Traditional Banking (Вестник КазНУ. Серия Экономическая, 2017)
The paper contribute to the research regarding the effectiveness of Islamicbanking in Kazakhstan. The comparative analysis of Islamic Banking and ConventionalBanking firmsis made. Moreover, it touch the differences of the IslamicBanks and Conventional Banks in terms of historical origin, mobilizing of financialresources, and ways of generating profit, operating principles, and equity structure.Methodological base of research in given clause was made with modernconcepts Islamic banking and Islamic model of financing adequacy, asset quality,management, earnings and liquidity as a whole. Findings of the results indicatethe mathematical model consists of a probability space, a Brownian motion and aPoisson process. The jumps are independent and identically distributed. The approachconsists of defining a notion of risk and production instrument asset qualityin order to minimize the risk. To empirically evaluate performance of the banks,different financial ratios are employed which are based on CAMEL frameworkduring the period 2011-2015. We measure performance in terms of capital adequacy,asset quality, management, earnings and liquidity. In this work, descriptivestatistics, one-way Annova and regression analysis are used to make hypothesistest and determine the ratio significance. Consequently, results from empiricalanalysis indicate that there is difference in profitability determinants.